2017
DOI: 10.1021/acs.iecr.7b03513
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transport Properties of CO2-Expanded Liquids: n-Hexane, n-Decane, and n-Tetradecane

Abstract: A number of processes involve liquids saturated with significant quantities of gases at elevated pressures, e.g., processes in gas- or CO2-expanded liquids (GXLs, CXLs), particle formation from gas or supercritical antisolvent methods (GAS, SAS, etc.), CO2 capture and sequestration, and enhanced oil recovery (EOR). In order to engineer these systems, the thermodynamic and transport properties are required. This contribution is one of the first reports for the heat transport properties of gas-expanded liquids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The nominal uncertainty associated with the thermal conductivity sensor given by the manufacturer is ±1%. However, we have measured the thermal conductivity of n ‐alkanes in a previous study 94 and found much less error; n ‐alkanes (e.g., C6–C14) have thermal conductivities that overlap those of the IL in this study. For instance, the difference between our measurements for n ‐hexane and n ‐tetradecane at three temperatures and well‐established experimental values had an average absolute relative deviation (AARD) of 0.25%.…”
Section: Experimental Methodsmentioning
confidence: 55%
See 4 more Smart Citations
“…The nominal uncertainty associated with the thermal conductivity sensor given by the manufacturer is ±1%. However, we have measured the thermal conductivity of n ‐alkanes in a previous study 94 and found much less error; n ‐alkanes (e.g., C6–C14) have thermal conductivities that overlap those of the IL in this study. For instance, the difference between our measurements for n ‐hexane and n ‐tetradecane at three temperatures and well‐established experimental values had an average absolute relative deviation (AARD) of 0.25%.…”
Section: Experimental Methodsmentioning
confidence: 55%
“…We have recently reported the thermal conductivities of CO 2 saturated n-alkanes. 94 Tomida et al 95 with CO 2 (Table 1) have been measured and reported in this study.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations